Heme Oxygenase 1 Induces Tau Oligomer Formation and Synapse Aberrations in Hippocampal Neurons. - Si, Zizhen; Wang, Xidi; Zhang, Zhujun; Wang, Jinxin; Li, Jihong; Li, Jing; Li, Ling; Li, Yuanxin; Peng, Yahui; Sun, Chongran; Hui, Yang; Gao, Xu (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by behavioral changes and cognitive decline. Recent evidence suggests that it is the soluble forms of tau oligomers (Tau-O) and Aβ oligomers (oAβ) rather than the well-studied insoluble protein aggregates that possess the neurotoxicity, infectivity, and amplification underlying disease progression. Heme oxygenase 1 (HO-1), an inducible enzyme upregulated in the cortex and hippocampus of AD brains, was reported to damage neural structures and disrupt brain function, suggesting possible contributions to Tau-O-mediated neurodegeneration. In this study, we focused on the effects of HO-1 on Tau-O formation. In hippocampus of HO-1-overexpressing transgenic mice and neural 2a (N2a) cells, Tau-O was co-localized with HO-1 as visualized by immunofluorescence staining. Furthermore, primary cultured hippocampal neurons from HO-1 transgenic mice showed elevated Tau-O and concomitant reductions in spine density and length as well as dendritic length, diameter, and arborization. Blocking Tau-O formation by isoprenaline reversed these HO-1-induced morphological changes. These results indicated that HO-1 contributes to Tau-O formation and ensuing synaptic damage. Thus, HO-1 is a promising target for AD drug development.